2014
DOI: 10.1016/j.marpolbul.2014.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Out of sight but not out of mind: Harmful effects of derelict traps in selected U.S. coastal waters

Abstract: There is a paucity of data in the published literature on the ecological and economic impacts of derelict fishing traps (DFTs) in coastal ecosystems. We synthesized results from seven NOAA-funded trap fisheries studies around the United States and determined that DFT-caused losses to habitat and harvestable annual catch are pervasive, persistent, and largely preventable. Based on this synthesis, we identified key gaps to fill in order to better manage and prevent DFTs. We conclude with suggestions for developi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 21 publications
0
35
0
1
Order By: Relevance
“…For example, Murray and Cowie (2011) demonstrated the presence of plastic microfibres shed from fishing net protectors in the intestines of >80 % of the commercially harvested prawns, an issue that could be well addressed by gear regulations. Arthur et al (2014) found that the number of crabs caught per derelict fishing trap per year ranged from 4 to 76 in selected US coastal waters. This issue could be addressed by designing traps (e.g.…”
Section: Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Murray and Cowie (2011) demonstrated the presence of plastic microfibres shed from fishing net protectors in the intestines of >80 % of the commercially harvested prawns, an issue that could be well addressed by gear regulations. Arthur et al (2014) found that the number of crabs caught per derelict fishing trap per year ranged from 4 to 76 in selected US coastal waters. This issue could be addressed by designing traps (e.g.…”
Section: Recommendationsmentioning
confidence: 99%
“…Kim et al (2014) estimated that 11,500 t of traps and 38,500 t of gill-nets are abandoned annually in Korean waters and suggested incentive programmes for fishermen to use ecofriendly gear designs. In addition, several measures could be adopted, including developing waste recycling practice among fishers, installing adequate PRFs, encouraging environmental education, promoting lost gear recovery, encouraging the use of environmentally friendly gear, promoting spatial management to reduce gear conflict and improving gear marking (Cho 2009;Macfadyen et al 2009;Chen and Liu 2013;Gold et al 2013;Arthur et al 2014). Some of these measures may also apply to other types of small vessels (e.g.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasingly durable materials used in fishing equipment means that it can continue to ghost fish for some time; in this way it presents particular challenges as marine waste. Fisheries incur costs, firstly in having to replace the fishing gear they have lost at sea, and secondly in a reduction in their potential harvestable catch, and indeed the sustainability of that catch (Butler et al 2013;Arthur et al 2014;Bilkovic 2014). One study in Puget Sound, Washington, estimated that over 175,000 dungeness crab (Metacarcinus magister) were killed each year by derelict fishing traps, equivalent to around €586,000 or 4.5 % of the average annual harvest (Antonelis 2011).…”
Section: Fisheriesmentioning
confidence: 99%
“…A significant proportion of marine litter originates from land-based sources; a global figure of 80 % is frequently cited, although the origins of this are unclear (Arthur et al 2014) and figures may vary considerably regionally. The National Marine Debris Monitoring Program, which analyzed marine litter on US beaches, 1 determined that 49 % was from land-based sources and 18 % from ocean-based sources, with a further 33 % for which the source could not be identified) (Ocean Conservancy 2007).…”
Section: Landfill Taxes/leviesmentioning
confidence: 99%